DD-MIC(O) preconditioning of rotated trilinear FEM elasticity systems - Georgiev, I.; Margenov, S. (Computer Assisted Methods in Engineering and Science, 2004)
New results about preconditioning of rotated trilinear nonconforming FEM elasticity systems in the case of mesh anisotropy are presented. The solver of the arising linear system is based on the constructed efficient preconditioner of the coupled stiffness matrix. Displacement decomposition of the stiffness matrix is used as a first step of the algorithm. At the second step, modified incomplete factorization MIC(O) with perturbation is applied to a proper auxiliary M-matrix to get an approximate factorization of the obtained block-diagonal matrix. The derived condition number estimates and the presented numerical tests well illustrate the behaviour of the theoretically studied algorithms as well as their robustness for some more realistic benchmark problems.